Highly Diastereoselective Reaction of α‐Diazoesters with Aryl Alcohols and Isatin Imines: Rapid Access to Oxindole‐Derived α‐Alkoxy‐β‐amino Acid Derivatives with Two Adjacent Quaternary Carbon Centers. Issue 11 (6th March 2014) - Rajasekaran, Tamilselvan; Karthik, Govindaraju; Sridhar, B.; Kumar, S. Kiran; Reddy, Basi V. Subba
Abstract: A stereoselective synthesis of oxindole‐derived α‐alkoxy‐β‐amino acid derivatives was achieved in high yield with excellent diastereoselectivity through the three‐component reaction of methyl 2‐diazoarylacetate, aryl alcohols, and isatin‐derived ketimines by using Rh2 (OAc)4 (1 mol‐%) as the catalyst. The products are very useful for the synthesis of analogues of the gastrin receptor antagonist AG‐041R, spirooxindolyl β‐lactams, the oxindole‐derived side chain of Taxol, and natural product cytoxazone and aminopyrrolo[2, 3‐ b ]indoline derivatives. Abstract : A Rh2 (OAc)4 ‐catalyzed, three‐component approach for the synthesis of a series of oxindole‐appended α‐alkoxy‐β‐amino acid derivatives is developed by using methyl 2‐diazoarylacetate, aryl alcohols, and isatin‐based ketimines. The reaction proceeds smoothly under mild conditions to give the desired product in high yields with excellent diastereoselectivity.